Effect of different factors on nitrogen solubility of coated urea - YE Xue-zhu; HE Ji-xiu; WANG Xiao-li; HE Nian-zu (浙江大学学报. 农业与生命科学版)
Two forms of coated urea (CU1, CU2) consisted of granule urea coated with high molecular polymer in different thickness were used to study the effect of soil moisture, ion concentration and temperature on nitrogen solubility. The results indicated that the nitrogen solubility of CU was affected by soil moisture contents and ion concentration of soil solution. Nitrogen release rate hardly changed when soil moisture reached to saturation or more. However, the higher the ion concentration of soil solution was, the less the nitrogen released. The nitrogen release rate was not affected by temperature.